2019
DOI: 10.24908/pocus.v4i2.13692
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Training for Family Medicine Residents: Examining the outcomes and feasibility of a pilot ultrasound curriculum

Abstract: It is estimated that 50% of deaths due to abdominal aortic aneurysms (AAA) could be prevented by a national screening program [1, 2, 3]. Thanks to technological advancements and cost reductions, point-of-care ultrasound (POCUS) in family medicine (FM) is becoming more prevalent [4, 5]. Despite the potential utility of POCUS in FM, of 224 FM residency programs surveyed, only 21% had developed a curriculum [6]. The main barriers identified to establishing a FM POCUS curriculum in Canadian FM residency programs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Assessments in these studies focused on very short-term knowledge and/or skill retention. Several studies have demonstrated longterm knowledge or confidence retention after several weeks or months [22,25,51,52], however, few studies have investigated long-term skill retention [22]. The importance of investigating long-term skill retention is evident both from the results of our pilot and our review of the literature.…”
Section: Single Primary Outcome Selection For a Definitive Studymentioning
confidence: 88%
“…Assessments in these studies focused on very short-term knowledge and/or skill retention. Several studies have demonstrated longterm knowledge or confidence retention after several weeks or months [22,25,51,52], however, few studies have investigated long-term skill retention [22]. The importance of investigating long-term skill retention is evident both from the results of our pilot and our review of the literature.…”
Section: Single Primary Outcome Selection For a Definitive Studymentioning
confidence: 88%